(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Emotional intelligence (EI) is increasingly recognised as a key determinant of leadership, teaching effectiveness, job satisfaction, and stress management in higher education. While prior research largely views EI as a personal trait, research on socio-demographic influences has received limited attention, particularly in the Indian context. This study examines differences in EI across age, gender, marital status, experience, employment status, income, educational qualification, and administrative roles among 106 faculty members from HEI in Telangana. A descriptive, cross-sectional design was employed, and data were collected using a structured questionnaire. Findings reveal significant variations in EI by age, experience, employment status, and income, with older, more experienced, regular employees, and those with higher incomes reporting greater EI. No significant differences emerged for gender, marital status, education, or administrative responsibility. The study highlights EI as a dynamic skill shaped by socio-demographic factors, emphasising its importance for implementing emotional interventions within institutional policies to foster emotional well-being and performance in HEIs.